Implementasi Program Pengembangan Kompetensi dan Dampaknya terhadap Keterikatan Karyawan: Perspektif Kualitatif dari Wawancara dengan Karyawan Lintas Generasi - Salsabilla Ardika Panjaitan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
The era of digitalization and technological transformation has introduced complex challenges for organizations in managing multigenerational human resources. Each generation—Baby Boomers, Generation X, Millennials, and Generation Z—has distinct characteristics, motivations, and expectations regarding learning and competency development. This study aims to analyze the implementation of competency development programs and their impact on employee engagement from a generational perspective using a qualitative approach. The research adopts an interpretivist paradigm and involves 28 employees representing the four generational cohorts. Data were collected through semi-structured in-depth interviews and analyzed using Braun and Clarke’s thematic analysis method to identify patterns of meaning from participants’ experiences. The findings reveal significant generational differences in learning preferences: younger generations tend to favor digital, interactive, and collaborative methods, while older generations appreciate traditional face-to-face mentoring and structured training. Five key factors were identified as influencing the effectiveness of competency development programs: (1) management support, (2) facilitator quality, (3) relevance and contextualization of materials, (4) training time flexibility, and (5) adaptive feedback systems. The priority level of each factor varied across generations, reflecting their specific learning needs and work expectations. The competency development programs also demonstrated varying impacts on the dimensions of employee engagement. Cognitive engagement increased most notably among younger employees, Generation X showed stronger emotional engagement, while Baby Boomers exhibited high levels of organizational commitment. Based on these insights, the study developed an integrative model outlining three strategic pathways to enhance cross-generational program effectiveness. Key recommendations include implementing a blended learning approach and fostering cross-generational collaboration as essential strategies to address the diverse learning styles and engagement drivers of a multigenerational workforce. This research highlights the importance of a nuanced and inclusive strategy for employee development in the digital era, ensuring that competency-building efforts are aligned with generational values and organizational goals.